Español Peru : España - Zegarra Malaga, Mackey_0802@hotmailcom (2022)
ABSTRACT: Objectives: To determine the association between maternal perinatal factors and early neonatal sepsis in a Chimbote hospital. Methodology: Analytical, cross-sectional, retrospective study and design of cases and controls. Fifty-one newborns with early neonatal sepsis (cases) and 51 healthy newborns (control) were compared, from the neonatology service of La Caleta hospital, period 2016-2020; using bivariate and multivariate statistics (odds ratio, 95% confidence interval, chi square and logistic regression p value). Results: The male sex was found to have an odds ratio: 2.07; 95% CI (0.93 to 4.61); prematurity odds ratio: 3.91, 95% CI (0.76 to 19.98); low birth weight odds ratio: 2.67, 95% CI (0.49 to 14.44); urinary tract infection odds ratio: 6.77, 95% CI (1.41 to 32.36); premature rupture of membranes> 18 hours odds ratio: 1.98, 95% CI (0.61 to 6.37); chorioamnionitis odds ratio: Undefined, 95% CI (Undefined); meconium amniotic fluid odds ratio: 7.37, 95% CI (1.98 to 27.31), acute fetal distress odds ratio: 12.25, 95% CI (1.50 to 99.80); and dystocic delivery odds ratio: 3.50, 95% CI (1.36 to 8.99). Conclusions: Presenting meconium amniotic fluid, acute fetal distress, dystocic delivery and urinary tract infection were risk factors associated with early neonatal sepsis. The evidence analyzed was not sufficient to conclude that the sex of the neonate, low birth weight, prematurity, chorioamnionitis, and prolonged rupture of membranes were risk factors for early neonatal sepsis.